Search broadly or search narrowly? Role of knowledge search strategy in innovation performance. Issue 5 (10th June 2019) - Li, Jian; Li, Yishu; Yu, Yue; Yuan, Ling
Abstract : Purpose: This paper aims to shed some new light on the mixed findings of previous empirical studies on the effect of knowledge search breadth (SB) on firms' 2019 innovation performance (IP). Design/methodology/approach: The paper adopts a contingent approach that examines the two organizational factors in determining the shape of the SB-IP curve. The empirical study is based on survey data gathered from 414 Chinese firms. In dealing with concerns on simultaneity and reverse causality, perceived time-lag between outcome variable and explanatory variables was introduced. Findings: This study reveals that knowledge novelty and absorptive capacity are two functions underlying the SB-IP relationship. The results also indicate that innovation orientation and firm age moderate the SB-IP relationship in different ways: the more innovation-oriented the firm, the steeper the inverted U-shaped SB-IP relationship will be, while the older the firm, the flatter the SB-IP relationship will be. Interestingly, there is strong evidence for the shape-flip phenomenon of the SB-IP curve: SB has an inverted U-shaped effect on IP when a firm is young; however, SB has a U-shaped effect when the firm is older than 37 years. Originality/value: By revealing two underlying functions and two moderators of the association between SB and IP at the firm level, this paper contributes to shed some new light to the mixed results reported by previous empirical studies that have examined the effect of knowledge search on firm innovation.